PENERAPAN TEKNOLOGI AEROPONIK BERBASIS PARTICIPATORY RURAL APPRAISAL (PRA) UNTUK PENINGKATAN GIZI DI MERAUKE - Ferry Irawan; Febry Ramadhani Suradji; Rosmala Widijastuti; Rival Hanip; Makmum Ashari (Universitas Negeri Makassar, 2026)
Nutritional problems and limited access to nutritious food remain challenges in several areas of Merauke Regency, particularly in Mandala District.. This community service activity aims to increase community capacity in utilizing aeroponic technology as an effort to strengthen nutritional improvements and sustainable food security. The implementation method uses the Participatory Rural Appraisal (PRA) approach that emphasizes active community involvement in every stage of the activity. The implementation stages include participatory problem identification, joint planning, training and demonstration of aeroponic technology, assistance in system management, and community participation-based evaluation. The target groups of the activity are community groups and housewives in Mandala District, Merauke Regency. The results of the activity show an increase in community knowledge and skills in plant cultivation using the aeroponic system, as well as an increase in the availability of fresh vegetables as a source of family nutrition. In addition, the community is starting to be able to manage the aeroponic system independently and sustainably. The PRA approach also encourages active community participation, thereby increasing their sense of ownership of the program being implemented. Thus, the application of aeroponic technology through the PRA approach is effective in supporting nutritional improvements and strengthening sustainable food security in Mandala District, Merauke.